IDENTITAS NASIONAL: KONTRIBUSI PROGRAM P5 DALAM KURIKULUM BARU GUNA MEMBANGUN RASA NASIONALISME ANAK SEKOLAH DASAR - Rambe, Novi Astika; Nasution, Liliana Agusfrina; Yunita, Sri; Dharma, Surya (JS (JURNAL SEKOLAH), 2024)
Abstract: The very rapid development of technology and the flow of globalization are things that must be considered and have an influence on the erosion of the sense of nationalism of future generations. The purpose of this research is to determine the contribution of the p5 program as a project to strengthen the profile of Pancasila students in schools towards a sense of nationalism. Indonesia is a pluralistic country that is rich in diversity in terms of ethnicity, religion, race and class. Diversity has many influences, such as gaps that can lead to conflict between groups or are caused by differences in culture and background between groups in society. So character cultivation is very necessary to provide understanding and strengthen the spirit of nationalism in students. The spirit of nationalism is a feeling of pride and love for one's country so that one is able to respect and respect the differences that exist in society. This research uses a literature study with a systematic review where data collection comes from textbooks, journals, scientific articles, and other literature reviews that are appropriate to the research study. The results of this research are regarding the contribution of implementing P5 activities through themes that are relevant to the need to build a sense of nationalism in students, especially at elementary school age.Keywords: National Identity, P5, Pancasila Student Profile, Sense of Nationalism, Globalization. Abstrak: Perkembangan teknologi yang sangat pesat dan arus globalisasi menjadi salah satu hal yang harus diperhatikan dan berpengaruh terhadap pengikisan rasa nasionalisme generasi kedepan. Tujuan adanya penelitian ini adalah untuk mengetahui kontribusi program p5 sebagai proyek penguatan profil siswa Pancasila di sekolah terhadap rasa nasionalisme. Indonesia adalah negara majemuk yang kaya akan keanekaragaman baik dari segi suku, agama, ras dan golongan. Keragaman memiliki banyak pengaruh, seperti kesenjangan yang dapat menimbulkan konflik antar kelompok atau disebabkan oleh perbedaan budaya dan latar belakang antar kelompok dalam masyarakat. Sehingga penanaman karakter sangat diperlukan untuk memberikan pemahaman dan memperkuat jiwa nasionalisme pada siswa. Semangat nasionalisme adalah rasa bangga dan cinta tanah air sehingga mampu menghargai dan menghargai perbedaan yang ada dalam masyarakat. Penelitian ini menggunakan studi pustaka dengan tinjauan sistematis dimana pengumpulan data berasal dari buku teks, jurnal, artikel ilmiah, dan kajian pustaka lain yang sesuai dengan kajian penelitian. Hasil dari penelitian ini yaitu mengenai kontribusi pelaksanaan kegiatan P5 melalui tema-tema yang diusung relevan dengan kebutuhan dalam membangun rasa nasionalisme peserta didik terlebih pada usia sekolah dasar. Kata Kunci: Identitas Nasional, P5, Profil Pelajar Pancasila, Rasa Nasionalisme, Globalisasi.